2023
DOI: 10.18632/aging.204602
|View full text |Cite
|
Sign up to set email alerts
|

Potential reversal of biological age in women following an 8-week methylation-supportive diet and lifestyle program: a case series

Abstract: Here we report on a case series of six women who completed a methylation-supportive diet and lifestyle program designed to impact DNA methylation and measures of biological aging. The intervention consisted of an 8-week program that included diet, sleep, exercise and relaxation guidance, supplemental probiotics and phytonutrients and nutritional coaching. DNA methylation and biological age analysis (Horvath DNAmAge clock (2013), normalized using the SeSAMe pipeline [a]) was conducted on blood samples at baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…These same DNA methylation signatures are also being used to investigate the impact of lifestyle factors such as diet and nutritional status on disease risk and aging (Quach et al, 2017;Lu et al, 2019;Fitzgerald et al, 2021) that may reveal potential therapeutic interventions to slow aging phenotypes and agerelated diseases, including cancer. Plant-based, Mediterranean, and methylation-supportive diets can rejuvenate DNA methylation aging signatures, decreasing chronological age predictions by 1-10 years in as little as 8 weeks of intervention (Gensous et al, 2020;Dwaraka et al, 2023;Fitzgerald et al, 2023).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…These same DNA methylation signatures are also being used to investigate the impact of lifestyle factors such as diet and nutritional status on disease risk and aging (Quach et al, 2017;Lu et al, 2019;Fitzgerald et al, 2021) that may reveal potential therapeutic interventions to slow aging phenotypes and agerelated diseases, including cancer. Plant-based, Mediterranean, and methylation-supportive diets can rejuvenate DNA methylation aging signatures, decreasing chronological age predictions by 1-10 years in as little as 8 weeks of intervention (Gensous et al, 2020;Dwaraka et al, 2023;Fitzgerald et al, 2023).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Second, our results showed that the difference between PhenoAge and chronological age after indexed to the local context had a relatively linear ‘dose-related’ relationship to hospital mortality that did not reach a plateau until up to a 20-year gap. Emerging studies have demonstrated that phenotypical age is more like a dynamic clock [ 5 ]; this would also mean that phenotypical age is like a quantitative assessment of physiological reserve, and there is an opportunity for interventions to ‘dial back’ the phenotypical age of critically ill patients, like non-critically ill patients [ 22 , 23 ]. A recent study also showed that Clonal Hematopoiesis of Indeterminate Potential (CHIP) had a direct correlation with biological age, including the PhenoAge [ 3 ], providing strong biological rationale to support the prognostic significance of PhenoAge.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, epigenetic clocks have been used in the randomized clinical trials to validate the effects of an interventions [ 47 ]. A series of subsequent clinical studies further emphasized the importance of studying potential changes in DNAm levels during aging [ 48 , 49 ]. In general, epigenetic age prediction is easier and more effective.…”
Section: Molecular Aging Biomarkersmentioning
confidence: 99%